الأمير ابن المشطوب الهكاري 575-619هـ/ 1179 – 1222 م سيرته و عصره - امین, نەبەز مجید (Sulaimani Journal for Humanities, 2000)
History is full of the biographies of the heros, each nation have their own heros whom they are proud of and of belonging to them, because of this the people of this nation can be proud of their past times and the biographies of their ancestors, in addition to this it will give them hope for the future because the nation that can give birth to a hero is able to give birth to other heros despite the long time and the events. AL- Hakari nation, during the period which we are concerning with studying one of their charaeters, gave birth to several princes who had outstandinpositions and were of world-wide fame. Among these princes (ibn AL-Mashtub AL-Hakari) whom I have chosen as a subject of my research. Idivided this research into four chapters:- The first chapter deals with the borning of this Kurdish prince, his growing up, qualities and surnames, he had a strong and a strong and fearful personality in a way that the kings were afraid of him… The scond chapter deals with the prince’s role in the internal disputes among the members of the Ayubian family, and his attitudes toward the kings of this family which was changing according to his own benefit. The third chapter deals with illustrating the prince’s attitude toward the fifth crusader’s campaign upon Egypt, and his attempts to remove the king Al-Kamil bin Al-Adil from the authority and appointing his brother (King Al-Fa’ez bin Al-Adil), but his attempt had failed and he was exiled to Syria. The fourth ehapter deals with Al-Hakari’s relationship with the king Al-Ashraf and other princes in Al-Jazirah, and the battles he rushed against his adversaries which ended with imprisoning him by the king Al-Ashraf and tormenting him till he died in his prison.